Identification and regulation of the long non-coding RNA Heat2 in heart failure. (January 2019) - Boeckel, Jes-Niels; Perret, Maya F.; Glaser, Simone F.; Seeger, Timon; Heumüller, Andreas W.; Chen, Wei; John, David; Kokot, Karoline E.; Katus, Hugo A.; Haas, Jan; Lackner, Maximilian K.; Kayvanpour, Elham; et al.
Abstract: Aims: Circulating immune cells have a significant impact on progression and outcome of heart failure. Long non-coding RNAs (lncRNAs) comprise novel epigenetic regulators which control cardiovascular diseases and inflammatory disorders. We aimed to identify lncRNAs regulated in circulating immune cells of the blood of heart failure patients. Methods and results: Next-generation sequencing revealed 110 potentially non-coding RNA transcripts differentially expressed in peripheral blood mononuclear cells of heart failure patients with reduced ejection fraction. The up-regulated lncRNA Heat2 was further functionally characterized. Heat2 expression was detected in whole blood, PBMNCs, eosinophil and basophil granulocytes. Heat2 regulates cell division, invasion, transmigration and immune cell adhesion on endothelial cells. Conclusion: Heat2 is an immune cell enriched lncRNA that is elevated in the blood of heart failure patients and controls cellular functions.